مخالفات المصفي - بوخالفة, حدة (جامعة الوادي University of Eloued, 2019)
الملخص يعتبر المصفي وكيلا للشركة و يتحمل كل إلتزامات الوكيل بأجر، و يسأل عن جميع المخلفات التي يرتكبها، حيث تقوم مسؤولية المصفي عن السلوكات الإجرامية التي إرتكبها خلال مرحلة التصفية بمناسبة عمله ، و هي القيام بالأفعال أو الإمتناعات المجرمة و المنصوص عليها في القانون التجاري ضمن مخالفات التصفية ، و قد حدد المشرع عقوبات تتناسب مع الأضرار التي لحقت بالشركاء أو المتعاملين مع الشركة ، حفاظا على حقوقهم . Abstract The liquidator shall be regarded as the agent of the company and shall bear all the obligations of the agent in remuneration, The liquidator is responsible for the criminal behavior he committed during the liquidation phase on the occasion of his work, namely the carrying out of the criminal acts or omissions stipulated in the Commercial Law in the liquidation contravention. The legislator has set penalties commensurate with the damages suffered by partners or dealers with the company, in order to preserve their rights.
Contravention Of The Liquidator
Keywords: مصفي ، الشركات التجارية ، الإستعمال التعسفي لأموال الشركة ، مخالفات التصفية; Liquidator, commercial enterprises, arbitrary use of company funds, Liquidation Contravention